Homogeneity of Ge1-xSix alloys (x≤0.30) grown by the travelling solvent method. (1st December 2004) - Labrie, D.; George, A.E.; Jamieson, M.; Obruchkov, S.; Healey, J.P.; Paton, B.E.; Saghir, M.Z.
Crystal growth of Ge1-x Six alloy with [Si] composition ranging from 1 to 30 at.%. using the travelling solvent method (TSM) is presented. Single crystal growth was obtained using a Ge seed crystal. The fluctuations in chemical composition along and transverse to the Ge1-xSix samples were typically less than ±0.4 and 0.3 at.%, respectively. The macroscopic composition inhomogeneities along the growth axis in the TSM grown samples correlate strongly with those within the Ge1-x Six feedrods which in turn depend markedly on the quenching rate of the molten alloy. Hall effect measurements indicate that there is a conductivity type reversal in the samples from n to p type with Si composition above 1 at.% in the alloy.